Quantification of biomechanical interactions between dressage horses and riders - Keener, L. E.; Levy, M. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Dressage, a sport based on qualitative observations, would benefit from quantitatively defining desirable interaction characteristics. In analyzing joint angles of ten riders on one horse, we found a moderately high negative correlation between rider's hip- and knee- angles, and the horse's stifle angle. In contrast, there was little relationship between rider angular kinematics and the horse's hock angle. Further research will need to be conducted to determine how these results differ between horses.